An Analysis of Service Experience And Perceived Value Influence on Patient's Satisification At Regional Public Hospitals In South Sulawesi Province - Ardianti Ardianti; Syahrir A Pasaringi; Fridawaty Rivai; Irwandy Irwandy; A Indahwaty Sidin; Yahya Thamrin; Andi Agus Mumang (ACHSM, 2024)
Background: The service experience and perceived value that occurs in every interaction between patient and service provider will influence the patient's satisfaction. This study aims to analyze the effect of service experience and perceived value on patient's satisfaction at Regional Public Hospitals in South Sulawesi, Indonesia. Methods: The method used in this study was cross sectional by distributing questionnaires to 270 outpatients and 266 inpatients as respondents. Sampling was carried out by using proportional stratified random sampling technique from each participating hospital. Data were analyzed using multiple linear regression tests. Results: The results showed that service experience had an effect on patient's satisfaction in inpatient care [β=0.598, t=3.163; p=0.002] and in outpatient care [β=0.13, t=2.89; p=0.004]. Perceived value had an effect on patient's satisfaction in inpatient care [β=0.323, t=1.709; p=0.04] and in outpatient care [β=0.108, t=2.391; p=0.017]. Conclusion: Service experience and perceived value impact patient satisfaction.